RESEARCH OF KEY PARAMETERS OF SOCIAL AND DEMOGRAPHIC DEVELOPMENT OF SOCIETY - L. Davletshina (Вестник университета)
In this scientific work an attempt of a research of the term «social and demographic development of society», rather new to scientific community, is made. Studying of various sources in the area of work gives the chance to suggest that rather wide range of the scientific approaches concerning understanding of the concept «social and demographic situation» was created. These works are devoted to a concept research through a prism of the territory and time. The performed work on the analysis of scientific publications allows to draw a conclusion that, despite prevalence of definitions «demography» and «sociology» separately, the questions connected with the characteristic of key parameters of social and demographic development of society are considered still sketchy. Such state of affairs defines need of search and systematization of new approaches to its assessment.